Summary of the Rights of Minority Shareholders of a Corporation - De La Piedra, Ricardo (2025)
With the Peruvian economy dynamic and in constant movement for almost three decades, and in a scenario in which foreign and local investors continue to invest in incorporated companies and ventures, it is of vital importance for lawyers and businessmen to have a brief that develops in a didactic way, by thresholds, the rights that every minority shareholder has by law in the most used corporate vehicle to carry out business in Peru: the corporation; as well as the possibilities that contractual freedom grants to regulate their interests through shareholders' agreements.